Rationality of Decision Making of a Cross-Provincial Truck Driver's Wife in the Household (Case Study of a Cross-Provincial Truck Driver's Wife in Medan City) - Aqila, Annisa Gita; Amal, Bakhrul Khair (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This study aims to determine the rationality of decision-making by wives of inter-provincial truck drivers in households in the city of Medan. This research is qualitative research with a descriptive approach. The data in this research was collected through interviews, observation and documentation. The data analysis technique uses 3 actions, namely data reduction, data presentation, and drawing conclusions. Determining informants in this research was carried out using snowball sampling so that 5 informants were obtained, all of whom were wives of cross-provincial truck drivers. The research results found that the rationality of decision-making by wives of cross-province truck drivers includes financial management, meeting primary and tertiary needs, occupational health and safety, children's education, and social activities. The results of this research are in line with James S. Coleman's rational choice theory, which states that as long as a person's actions aim to achieve their goals, rational choice theory considers these actions to be rational, as reflected in the research results, that every decision taken by the wife is based on a specific goal.